Different efficiencies in foreign language learning for gamification and ludicization regarding learning outcome, readiness, engagement, and academic buoyancy - Zhang, Qi (Education and information technologies, 2025)
This study aims to investigate and compare the efficiencies of gamification and ludicization in foreign language learning regarding learning outcome, readiness, engagement, and academic buoyancy. Regarding the theoretical frameworks, gamification and ludicization, feasible in foreign language learning through interaction and problem-solving orientation, are conceptually different in transformation, elements, and reflexive space, eliciting the assumption about different effects of gamification and ludicization on foreign language learning from the perspectives of effect positivity and effect duration. Considering the method, this study employs a longitudinal between-subjects experiment including repeated measures of the involved variables, whose results are analyzed through the results of the Kruskal–Wallis H test and Wilcoxon signed ranks tests. According to the results, the facilitating instantly-after-intervention effects on the variables are overall stronger for gamification than ludicization, but the facilitating effects are overall more persistent for ludicization than gamification after an interval from the interventions. The conclusion is that gamification and ludicization show different efficiencies in foreign language learning regarding their conceptual differences and distinct empirical effects. While gamification highlights instant and temporary stimuli-response influences on language learning, ludicization emphasizes progressive and persistent cultivations of spontaneity for language learning.